Parenting with love and logic ebook Teaching children responsibility. - Cline, Foster (2014)
This parenting book shows you how to raise self-confident, motivated children who are ready for the real world. Learn how to parent effectively while teaching your children responsibility and growing their character. Establish healthy control through easy-to-implement steps without anger, threats, nagging, or power struggles. Indexed for easy reference.